2004
DOI: 10.1002/marc.200400106
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Ring‐Opening Polymerization of D,L‐Lactide by Microwaves

Abstract: Summary: Poly(D,L‐lactide) with a molar mass of 105 g · mol−1 and a yield over 90% was produced in 10 min by the ring‐opening polymerization of D,L‐lactide under microwave irradiation with forward power of 255 W. A degradation of the poly(D,L‐lactide) was also induced by microwaves with a power level over 340 W. The molar mass of poly(D,L‐lactide) was dependent upon the competition between the polymerization of D,L‐lactide and the degradation of the resulting polymer.Profiles of molar mass versus microwave irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 13 publications
1
36
0
1
Order By: Relevance
“…Optimal results were achieved setting the power level at 255 W, while reactions carried out at 340 W or more showed a significant degradation of the product (C. Zhang et al, 2004). According to other authors, the reaction rate in the ROP of L-lactide increases linearly with power output (tested up to 1,300 W), though molecular weights (and consequently degradation phenomena) were not monitored for P(L)LA (Koroskenyi & McCarthy, 2002).…”
Section: Scheme 2 Synthetic Routes To High Mw Poly(lactic Acid)mentioning
confidence: 97%
“…Optimal results were achieved setting the power level at 255 W, while reactions carried out at 340 W or more showed a significant degradation of the product (C. Zhang et al, 2004). According to other authors, the reaction rate in the ROP of L-lactide increases linearly with power output (tested up to 1,300 W), though molecular weights (and consequently degradation phenomena) were not monitored for P(L)LA (Koroskenyi & McCarthy, 2002).…”
Section: Scheme 2 Synthetic Routes To High Mw Poly(lactic Acid)mentioning
confidence: 97%
“…They reported that efficient heating using microwave resulted in successful polymerization without the need for vacuum or inert atmosphere (32). Liu and coworkers investigated the microwave assisted polymerization of lactide emphasizing on the effect of microwave power on polymerization process (31). They concluded that, up to 255 W the molecular weight of the polymer increased and reached a maximum when approximately 90% conversion was reached ( Figure 4) (31).…”
Section: Microwave-assisted Ring Opening Polymerization (5)mentioning
confidence: 98%
“…[7][8][9][10][11] Some polymerization reactions are significantly improved under microwave irradiation and the microwave-assisted preparations of biodegradable polymers have also been studied. [12,13] Poly(alkylene hydrogen phosphonate)s are a relatively new family of biodegradable polymers. Polymers of this type with molecular weights ranging between 2 000 and 5 000 Da have been actively investigated in the last few years, mainly for various biomedical applications.…”
Section: Introductionmentioning
confidence: 99%